2010
DOI: 10.1111/j.1443-1661.2010.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Small Gastrointestinal Stromal Tumor of the Stomach Showing Rapid Growth and Early Metastasis to the Liver

Abstract: A 65-year-old man received upper gastrointestinal endoscopy. At that time, no abnormalities were identified in the stomach except for a submucosal tumor approximately 1 cm in maximal diameter at the gastric cardia. Two months later, he developed tarry stools and anemia. Colonoscopy revealed no abnormal findings in the colon or terminal ileum. Upper gastrointestinal endoscopy was re-evaluated in our hospital. Macroscopically, the previously detected submucosal tumor had grown to 3.0 cm in maximal diameter and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 8 publications
1
24
0
2
Order By: Relevance
“…If initial cytohistological assessment of early gastric GIST has not been performed or has not been conclusive and if there is strong clinical suspicion of early GIST, endoscopic ultrasound of the stomach should be repeated already after an interval of 2-3 mo. This short interval is not due to the (very low) probability of rapidly progressive GIST [30] but takes into account the (low) risk of a subepithelial lesion different from GIST. The correct evaluation of a subepithelial lesion by endoscopic ultrasound relies on an experienced team of endoscopists.…”
Section: Endoscopic Surveillancementioning
confidence: 99%
“…If initial cytohistological assessment of early gastric GIST has not been performed or has not been conclusive and if there is strong clinical suspicion of early GIST, endoscopic ultrasound of the stomach should be repeated already after an interval of 2-3 mo. This short interval is not due to the (very low) probability of rapidly progressive GIST [30] but takes into account the (low) risk of a subepithelial lesion different from GIST. The correct evaluation of a subepithelial lesion by endoscopic ultrasound relies on an experienced team of endoscopists.…”
Section: Endoscopic Surveillancementioning
confidence: 99%
“…1,2,5 However, rapid growth of such tumors was reported, and accurate prediction remains difficult. 41 Management strategies, including tissue sampling of subepithelial lesions !2 cm, may need to be revised. 27 Therefore, tumors !20 mm (n Z 15) were included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that tumors 2 cm or less in diameter have no risk of postoperative metastasis. However, metastasis has been associated with even small GISTs[12]. It is therefore difficult to conclude that small tumors are benign.…”
Section: Discussionmentioning
confidence: 99%